O nieoczywistościach relacji między olbrzymami a karłami – zamyślenia na marginesie filozofii kultury Floriana Znanieckiego - Budajczak, Marek (Rocznik Pedagogiczny, 2021)
The article, recalling the work of Florian Znaniecki, reflects on hierarchizations of cultures. The part of it discusses some weaknesses of the language of sociology, i.e. the inconsistencies in defining and academic use of the concept of “culture”.